2011
DOI: 10.1007/s10237-011-0315-1
|View full text |Cite
|
Sign up to set email alerts
|

Live en face imaging of aortic valve leaflets under mechanical stress

Abstract: Soft tissues, such as tendons, skin, arteries, or lung, are constantly subject to mechanical stresses in vivo. None more so than the aortic heart valve that experiences an array of forces including shear stress, cyclic pressure, strain, and flexion. Anisotropic biaxial cyclic stretch maintains valve homeostasis; however, abnormal forces are implicated in disease progression. The response of the valve endothelium to deviations from physiological levels has not been fully characterized. Here, we show the design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…While no gross calcification may be present, the valve endothelium exhibits non-negligible inflammatory activation 55-58 Paruchuri et al identified clonally isolated sub-populations of human pulmonary VEC that were capable of EndMT in response to TGFβ, which supports our findings in pure whole VEC populations 59 . Holliday et al recently showed that in vitro cultured human aortic VEC isolated from heart transplant surgeries express endothelial phenotype markers and elevated α-SMA, which is in contrast to in vivo expression patterns in non-diseased human and porcine aortic valves 16,60-62 . These co-expression findings suggest that human aortic valve endothelium from these patients may have an increased propensity or capacity for EndMT 60 .…”
Section: Discussionmentioning
confidence: 99%
“…While no gross calcification may be present, the valve endothelium exhibits non-negligible inflammatory activation 55-58 Paruchuri et al identified clonally isolated sub-populations of human pulmonary VEC that were capable of EndMT in response to TGFβ, which supports our findings in pure whole VEC populations 59 . Holliday et al recently showed that in vitro cultured human aortic VEC isolated from heart transplant surgeries express endothelial phenotype markers and elevated α-SMA, which is in contrast to in vivo expression patterns in non-diseased human and porcine aortic valves 16,60-62 . These co-expression findings suggest that human aortic valve endothelium from these patients may have an increased propensity or capacity for EndMT 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the above studies have investigated the mechanobiological effects of pressure in isolation, 66,67,95,117 it must be noted that pressure causes increased stretch on the leaflets through tensile-compressive and bending forces. Hence, future studies must investigate these two forces in combination, rather than in isolation.…”
Section: Mechanical Environment and Mechanobiology Of Avmentioning
confidence: 99%
“…32 Cell level effects are investigated by isolating the cells 36 and subjecting them to strain or by using imaging techniques to investigate the cell behavior while the entire AV leaflet tissue is stretched. 66 Even though different strain levels have been used in various in vitro and ex vivo studies to elucidate cell level effects, it has been established that non-physiological strain leads to pathological conditions in AV leaflets in terms of inflammation, remodeling, and calcification.…”
Section: Mechanical Environment and Mechanobiology Of Avmentioning
confidence: 99%
See 1 more Smart Citation
“…Ex vivo bioreactor cultivation of native valvular tissues [19][20][21][22] and the in vitro application of stretch or defined substrate stiffness to VICs [23][24][25] and VIC-based engineered tissues [26,27] have collectively demonstrated that the VIC phenotype can be modulated by the mechanical environment [28,29]. Nevertheless, how heart valve leaflet tissue-level stresses and strains manifest locally at the cellular level remains unclear.…”
mentioning
confidence: 99%